Nanotechnology in dentistry: Current state and future perspectives - Lainović Tijana; Blažić Larisa; Potran Michal (Stomatološki glasnik Srbije, 2012)
Nanotechnology has been considered as multidisciplinary field of scientific research about different types of nanoparticles as well as the application of new nanomaterials and nanodevices in numerous areas of human interest. It offers advances in industry, engineering, information and communication technology, electronics, environmental science and energy savings, economics etc. New nanoproducts and nanotehnology could be applied in almost all fields of human activity. Potential benefit of nanomaterials and nanorobots applied in medicine and dentistry is of main concern when thinking about nanoadvances. However, nanotechnology has become a controversial issue between scientific and public opinions due to the insufficient knowledge of potential hazard to human health and environment. Some of the raised questions are what are the advantages and disadvantages of nanotechnological evolution, and what kind of future can be expected when changes gain wider scale? The aim of this study was to present the importance of nanotechnology in various areas, especially in medicine and dentistry, and to point out possible consequences of their use to human health and environment.